Question
upstudy study bank question image url

Given the system of equations, what is the value of the \( y \)-determinant? \( \begin{array}{l}3 x+y-10=0 \\ 4 x-y-4=0 \\ -14 \\ 28 \\ -28\end{array} \)

Ask by Ingram Brewer. in the United States
Feb 27,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The \( y \)-determinant is \(-7\).

Solution

To find the value of the \( y \)-determinant for the given system of equations, we first need to express the system in a standard form and then calculate the determinant of the coefficient matrix. The given equations are: 1. \( 3x + y - 10 = 0 \) 2. \( 4x - y - 4 = 0 \) We can rewrite these equations in the standard form \( Ax + By = C \): 1. \( 3x + y = 10 \) 2. \( 4x - y = 4 \) Now, we can represent this system in matrix form \( A \mathbf{x} = \mathbf{b} \), where: \[ A = \begin{pmatrix} 3 & 1 \\ 4 & -1 \end{pmatrix}, \quad \mathbf{x} = \begin{pmatrix} x \\ y \end{pmatrix}, \quad \mathbf{b} = \begin{pmatrix} 10 \\ 4 \end{pmatrix} \] Next, we will calculate the determinant of the coefficient matrix \( A \): \[ \text{det}(A) = \begin{vmatrix} 3 & 1 \\ 4 & -1 \end{vmatrix} \] The determinant can be calculated using the formula: \[ \text{det}(A) = ad - bc \] where \( a = 3, b = 1, c = 4, d = -1 \). Now, let's calculate the determinant: \[ \text{det}(A) = (3)(-1) - (1)(4) = -3 - 4 = -7 \] Thus, the value of the \( y \)-determinant is \(-7\).

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Extra Insights

To find the value of the \( y \)-determinant, let's first rearrange the given system of equations into a more manageable form. The two equations can be expressed as: 1. \( y = 10 - 3x \) 2. \( y = 4x - 4 \) Setting these equal to each other gives us: \[ 10 - 3x = 4x - 4 \] Now, let's solve for \( x \): \[ 10 + 4 = 4x + 3x \] \[ 14 = 7x \implies x = 2 \] Substituting \( x = 2 \) back into one of our original equations to find \( y \): \[ y = 10 - 3(2) = 10 - 6 = 4 \] Now, to create a \( y \)-determinant, the solution involves constructing a determinant from the coefficients of the variables in the original system of equations. So, here is how we build the determinant: Using the coefficients from \[ \begin{array}{rl} 3x + y & = 10 \\ 4x - y & = 4 \end{array} \] We can write the determinant for the coefficients of \( y \): \[ D_y = \begin{vmatrix} 3 & 1 \\ 4 & -1 \end{vmatrix} = (3)(-1) - (1)(4) = -3 - 4 = -7 \] Thus, the value of the \( y \)-determinant is \(-7\).

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy